Method for producing silica sol and silica sol
Patent Information
- Application Number
- CN202610323469.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-19
- Filing Date
- 2026-03-17
- Publication Date
- 2026-09-22
Smart Images

Figure FT_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing silica sol and silica sol itself. Background Technology
[0002] Previously, chemical mechanical polishing (CMP) was used to polish the surfaces of materials such as metals, semi-metals, non-metals, and their oxides using polishing compositions. These polishing compositions are typically composed of an aqueous solution with chemical polishing properties and particles (abrasives) with mechanical polishing properties, using silica sol as the abrasive. In this case, by shaping the silica particles, good polishing performance can be achieved.
[0003] Japanese Patent Application Publication No. 2018-168031 (corresponding to US Patent No. 2020 / 0377371) discloses a method for manufacturing silica sol as a method for shaping silica particles. The method includes a step of mixing liquid (B) with liquid (A) to prepare a reaction solution. Liquid (A) comprises an alkaline catalyst, water, a first organic solvent, and silica particles for associativity. Liquid (B) comprises at least one of tetramethoxysilane and its condensate, and a second organic solvent. In the mixing, the addition rate of liquid (B) relative to 1 mol of water contained in liquid (A) is 8.5 × 10⁻⁶ silicon atoms. -4 ~5.6×10 -3 mol / min. Summary of the Invention
[0004] The technology described in Japanese Patent Application Publication No. 2018-168031 (corresponding to US Patent No. 2020 / 0377371) can obtain a silica sol containing highly associated silica particles, which can improve the grinding speed. However, for example, when the purpose is to reduce the haze value, it is required to increase the proportion of silica particles with a high aspect ratio in the silica sol.
[0005] Therefore, the present invention has been made in view of the above circumstances, and its object is to provide a method for manufacturing silica sol that can increase the proportion of silica particles with a high aspect ratio.
[0006] The inventors have conducted in-depth research on the aforementioned issues. Their findings indicate that the aforementioned effects can be achieved through the following method for manufacturing silica sol, thus completing this invention. The method for manufacturing silica sol includes: continuously or intermittently mixing liquid (B) in liquid (A), wherein liquid (A) comprises an alkaline catalyst, water, and a first organic solvent, and liquid (B) comprises at least one of tetramethoxysilane and its condensate, and a second organic solvent; the mixing includes: increasing the conductivity of the mixture after silica particles are formed in the mixture. Attached Figure Description
[0007] Figure 1 This is a diagram illustrating the method for determining the longest diameter of primary silica particles. Detailed Implementation
[0008] The following describes one embodiment of the present invention. The present invention is not limited to the following embodiment, and various modifications can be made within the scope of the claims. The embodiments described in this specification can be combined in any way to form other embodiments.
[0009] In this instruction manual, the range "X~Y" means "above X and below Y". Furthermore, unless otherwise specified, the operation and physical properties are measured at room temperature (20~25°C) and relative humidity 40~50%RH.
[0010] <Method for manufacturing silica sol>
[0011] One aspect of the present invention relates to a method for manufacturing silica sol, comprising: continuously or intermittently mixing a liquid (B) into a liquid (A), said liquid (A) comprising an alkaline catalyst, water, and a first organic solvent, said liquid (B) comprising at least one of a tetramethoxysilane and its condensate, and a second organic solvent, said mixing comprising: increasing the electrical conductivity of said liquid after silica particles are formed in the mixture. According to this aspect, a method for manufacturing silica sol capable of increasing the proportion of silica particles having a high aspect ratio is provided. With this configuration, a silica sol comprising a large number of silica particles having a high aspect ratio can be provided.
[0012] In this specification, a silica sol containing silica particles with a high aspect ratio refers to a silica sol in which the silica particles have an average aspect ratio of 1.5 or higher. Preferably, the silica particles in the silica sol of this type have an average aspect ratio of 1.5 or higher and an average sphericity of 0.80 or lower. The average aspect ratio and average sphericity will be explained in the section on silica sol described later.
[0013] In this specification, a silica sol containing a large number of silica particles with a high aspect ratio is defined as a silica sol in which the number of silica particles with an aspect ratio of 1.50 or higher accounts for 40% or more of the total number of silica particles in the silica sol. The proportion of silica particles with an aspect ratio of 1.50 or higher in the silica sol relative to the total number of silica particles will be explained later in the section on silica sol.
[0014] In this specification, "at least one of tetramethoxysilane and its condensate" will also be referred to as "tetramethoxysilane, etc."
[0015] The reason for achieving the above effect through this manufacturing method may not be clear, but it is believed to be as follows.
[0016] In this manufacturing method, when mixing liquid (B) with liquid (A), tetramethoxysilane and the like hydrolyze and condense in the mixture to form silica particles. It is believed that after the silica particles are formed, by increasing the conductivity of the mixture, the silica particles can easily bond together via the hydrolyzed tetramethoxysilane and the like, thus obtaining silica particles with a high aspect ratio.
[0017] The above mechanism is based on speculation, and its correctness or incorrectness does not affect the technical scope of the present invention.
[0018] The following describes the constituent elements of the method for manufacturing silica sol according to this method.
[0019] The method for manufacturing silica sol of this manner includes: continuously or intermittently mixing liquid (B) into liquid (A), said liquid (A) comprising an alkaline catalyst, water and a first organic solvent, said liquid (B) comprising at least one of tetramethoxysilane and its condensate, and a second organic solvent, said mixing comprising: increasing the electrical conductivity of said mixture after silica particles are formed in the mixture.
[0020] In this specification, "mixture" includes the mixture when mixed with liquid (B) in liquid (A), and the mixture when mixed with liquid (B) in liquid (A) and liquid (C) described later.
[0021] The method for manufacturing silica sol in this manner includes: continuously or intermittently mixing liquid (B) into a liquid (A) (mixing step), wherein the mixing step includes increasing the conductivity of the mixture after silica particles are formed in the mixture, i.e., during the process. Specifically, the mixing step of this method includes: continuously or intermittently mixing liquid (B) into liquid (A) to form silica particles in the mixture (silica particle formation step); increasing the conductivity of the mixture after the silica particle formation step (conductivity increase step); and continuously or intermittently mixing liquid (B) into the mixture after the conductivity increase step to allow the silica particles in the mixture to bond and grow (silica particle growth step).
[0022] From the viewpoint of easily generating high-purity silica sol (high-purity silica sol), the silica sol manufacturing method of this method preferably uses the sol-gel method. In a preferred embodiment, the silica particle formation step and the silica particle growth step in the silica sol manufacturing method of this method use the sol-gel method.
[0023] (Silica particle formation process)
[0024] In the silica particle forming process, liquid (B) is continuously or intermittently mixed into liquid (A) to form silica particles in the mixture, wherein liquid (A) comprises an alkaline catalyst, water and a first organic solvent, and liquid (B) comprises at least one of tetramethoxysilane and its condensate, and a second organic solvent.
[0025] Liquid (A) comprises an alkaline catalyst, water, and a first organic solvent. In addition to the alkaline catalyst, water, and the first organic solvent, liquid (A) may also contain other components, provided that the effects of the invention are not impaired.
[0026] In a preferred embodiment, the liquid (A) is composed of an alkaline catalyst, water, and a first organic solvent. By making the liquid (A) composed of an alkaline catalyst, water, and a first organic solvent, impurities contained in the mixture can be greatly reduced. Therefore, when the silica sol obtained by this manufacturing method is used as a polishing slurry, the influence of impurities on polishing can be suppressed. Furthermore, it can also be used for polishing objects such as silicon wafers and device wafers where metallic impurities are undesirable, providing a polishing slurry with wide applicability.
[0027] As the alkaline catalyst contained in the liquid (A), conventionally known substances can be used. From the viewpoint of minimizing the contamination of metal impurities, examples of alkaline catalysts include: ammonium salts such as ammonia and tetramethylammonium hydroxide, ethylenediamine, diethylenetriamine, triethylenetetramine, urea, monoethanolamine, diethanolamine, triethanolamine, tetramethylguanidine, etc. Among these, from the viewpoint of excellent catalytic activity, ammonium salts such as ammonia and tetramethylammonium hydroxide are more preferred, and ammonia is even more preferred. Ammonia has high volatility, so it can be easily removed during the manufacture of silica sol. It should be noted that the alkaline catalyst can be used alone or in combination of two or more. In addition, the alkaline catalyst can be in the form of an aqueous solution.
[0028] From the viewpoint of minimizing the introduction of metal impurities, etc., the water contained in the liquid (A) is preferably pure water or ultrapure water. When the above-mentioned alkaline catalyst is in the form of an aqueous solution, the water contained therein is the same as that contained in the liquid (A). Therefore, the water contained in the aqueous solution of the alkaline catalyst is also preferably pure water or ultrapure water.
[0029] The first organic solvent contained in the liquid (A) is preferably a hydrophilic organic solvent. Specifically, examples include alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, and 1,4-butanediol; and ketones such as acetone and methyl ethyl ketone. The first organic solvent may be used alone or in combination with two or more other solvents.
[0030] Alcohols are preferred as the first organic solvent. Using alcohols allows for easy replacement of both alcohols and water during the water replacement step described later, thanks to the ability to do so via heating and distillation. Furthermore, from the viewpoint of organic solvent recovery and reuse, methanol is preferred as the first organic solvent.
[0031] The contents of the alkaline catalyst, water and the first organic catalyst in the liquid (A) are not particularly limited, but can be appropriately adjusted, for example, to make the average secondary particle size of the silica particles formed in the mixture a desired value.
[0032] From the viewpoint of its role as a hydrolysis catalyst or the growth of silica particles, the lower limit of the content of the alkaline catalyst (e.g., ammonia) in the liquid (A) relative to the total amount of liquid (A) (100% by mass) is, for example, 0.1% by mass or more, preferably 0.3% by mass or more. The lower limit of the content of the alkaline catalyst (e.g., ammonia) relative to the total amount of liquid (A) (100% by mass) can be 0.5% by mass or more, 1.0% by mass or more, or 2.0% by mass or more. There is no particular limitation on the upper limit of the content of the alkaline catalyst (e.g., ammonia). From the viewpoint of productivity and cost, the upper limit of the content of the alkaline catalyst (e.g., ammonia) relative to the total amount of liquid (A) (100% by mass) is preferably 50% by mass or less. The upper limit of the content of the alkaline catalyst (e.g., ammonia) relative to the total amount of liquid (A) (100% by mass) can be 40% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less. The content of the alkaline catalyst (e.g., ammonia) relative to the total liquid (A) (100% by mass) can be 0.1% by mass or more and 50% by mass or less, 0.3% by mass or more and 40% by mass or less, 0.5% by mass or more and 20% by mass or less, 1.0% by mass or more and 15% by mass or less, 1.0% by mass or more and 10% by mass or less, 1.0% by mass or more and 5% by mass or less, 2.0% by mass or more and 15% by mass or less, 2.0% by mass or more and 10% by mass or less, or 2.0% by mass or more and 5% by mass or less.
[0033] The water content in liquid (A) is adjusted according to the amount of tetramethoxysilane or its condensate used in the reaction. From the viewpoint of the hydrolysis of tetramethoxysilane, the lower limit of the water content relative to the total amount of liquid (A) (100% by mass) is preferably 5% by mass or more. From the viewpoint of compatibility with liquid (B), the upper limit of the water content relative to the total amount of liquid (A) (100% by mass) is preferably 50% by mass or less, more preferably 40% by mass or less. The upper limit of the water content relative to the total amount of liquid (A) (100% by mass) can be 20% by mass or less or 15% by mass or less. The water content relative to the total amount of liquid (A) (100% by mass) can be 5% by mass or more and 50% by mass or less, 5% by mass or more and 40% by mass or less, 5% by mass or more and 20% by mass or less, or 5% by mass or more and 15% by mass or less.
[0034] From the viewpoint of compatibility with liquid (B), the lower limit of the content of the first organic solvent (e.g., methanol) in liquid (A) relative to the total amount of liquid (A) (100% by mass) is preferably 10% by mass or more, more preferably 20% by mass or more. The lower limit of the content of the first organic solvent (e.g., methanol) relative to the total amount of liquid (A) (100% by mass) can be 50% by mass or more, 75% by mass or more, or 85% by mass or more. From the viewpoint of dispersibility, the upper limit of the content of the first organic solvent (e.g., methanol) relative to the total amount of liquid (A) (100% by mass) is preferably 98% by mass or less, more preferably 95% by mass or less. The upper limit of the content of the first organic solvent (e.g., methanol) can be 94% by mass or less, 93% by mass or less, or 92% by mass or less. The content of the first organic solvent (e.g., methanol) relative to the total amount of liquid (A) (100% by mass) can be 10% by mass or more and 98% by mass or less, 20% by mass or more and 95% by mass or less, 50% by mass or more and 95% by mass or less, 75% by mass or more and 95% by mass or less, or 85% by mass or more and 95% by mass or less.
[0035] There are no particular limitations on the method of manufacturing liquid (A). For example, a method can be used to stir and mix the alkaline catalyst, water, a first organic solvent, and other components as needed.
[0036] Liquid (B) comprises at least one of tetramethoxysilane and its condensate, and a second organic solvent. In addition to comprising at least one of tetramethoxysilane and its condensate, and the second organic solvent, liquid (B) may also contain other components without impairing the effects of the invention.
[0037] In a preferred embodiment, the liquid (B) is composed of at least one of tetramethoxysilane and its condensate, and a second organic solvent. By making the liquid (B) composed of at least one of tetramethoxysilane and its condensate, and a second organic solvent, impurities contained in the mixture can be greatly reduced. Therefore, when the silica sol obtained by this manufacturing method is used as a polishing slurry, the influence of impurities on polishing can be suppressed. Furthermore, it can also be used for polishing objects such as silicon wafers and device wafers where metallic impurities are undesirable, providing a polishing slurry with wide applicability.
[0038] One type of tetramethoxysilane or its condensate may be used in liquid (B), or two or more types may be used in combination. Among them, tetramethoxysilane is preferred from the viewpoint of having suitable hydrolytic reactivity.
[0039] As the second organic solvent contained in liquid (B), a hydrophilic organic solvent is preferred. Specifically, examples include alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, and 1,4-butanediol; and ketones such as acetone and methyl ethyl ketone. The second organic solvent can be used alone or in combination with two or more other solvents.
[0040] Alcohols are preferred as the second organic solvent. By using alcohols, the water replacement step described later can be performed with the advantage of easily replacing alcohols and water through heating and distillation.
[0041] Among alcohols, at least one of methanol, ethanol, and isopropanol is particularly preferred. From the viewpoint of organic solvent recovery and reuse, methanol produced by the hydrolysis of tetramethoxysilane is even more preferred.
[0042] There are no particular restrictions on the content of tetramethoxysilane and other second organic solvents in liquid (B), for example, it can be appropriately adjusted to make the average secondary particle size of the silica particles formed in the mixture a desired value.
[0043] The lower limit of the content of tetramethoxysilane and the like in liquid (B) is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit of the content of tetramethoxysilane and the like is preferably 98% by mass or less, more preferably 95% by mass or less, further preferably 90% by mass or less, and particularly preferably 85% by mass or less. The content of tetramethoxysilane and the like is preferably 50% by mass or more and 98% by mass or less, more preferably 60% by mass or more and 95% by mass or less, further preferably 70% by mass or more and 90% by mass or less, and particularly preferably 75% by mass or more and 85% by mass or less.
[0044] The lower limit of the content of the second organic solvent (e.g., methanol) in liquid (B) is preferably 2% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, and particularly preferably 15% by mass or more. The upper limit of the content of the second organic solvent (e.g., methanol) is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less, and particularly preferably 25% by mass or less. The content of the second organic solvent (e.g., methanol) is preferably 2% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 40% by mass or less, further preferably 10% by mass or more and 30% by mass or less, and particularly preferably 15% by mass or more and 25% by mass or less.
[0045] If the content of tetramethoxysilane and other second organic solvents in liquid (B) is within the above range, the miscibility when mixed with liquid (A) can be improved.
[0046] The tetramethoxysilane condensate in liquid (B) is, for example, a 2-12 polymer, preferably a 4-8 polymer.
[0047] There are no particular limitations on the method of manufacturing liquid (B). From the viewpoint of miscibility, the preferred method for manufacturing liquid (B) is to stir and mix tetramethoxysilane and other components as needed in a second organic solvent.
[0048] In the silica particle forming process, liquid (B) is continuously or intermittently mixed in liquid (A). If liquid (B) is added to liquid (A) and mixed, tetramethoxysilane and the like are hydrolyzed and condensed in the mixture, thereby generating silica particles.
[0049] "Continuous mixing" means adding and mixing the liquid continuously, rather than adding and mixing the entire amount of liquid at once.
[0050] "Intermittent mixing" means adding and mixing the liquid in two or more separate steps, rather than adding and mixing the entire amount of liquid at once.
[0051] In the silica particle forming process, the stirring liquid (A) and the mixture are preferred. There are no particular limitations on the stirring speed, for example, it is above 30 rpm and below 500 rpm.
[0052] In the silica particle formation process, the addition rate of liquid (B) is not particularly limited and can be adjusted appropriately within a range that does not produce a gel-like substance. For example, relative to 1 mol of water contained in liquid (A), the addition rate of liquid (B), converted to silicon atoms, is 8.5 × 10⁻⁶. -4 mol / min or higher and 5.6 × 10 -3 Below mol / min. Silicon atom conversion refers to defining the number of moles of silicon atoms contained in tetramethoxysilane and its condensates as the total number of moles of tetramethoxysilane and its condensates. For example, 1 mole of tetramethoxysilane is equivalent to 1 mole of silicon atoms. Furthermore, when the condensate of tetramethoxysilane is a tetramer, 1 mole of the condensate is equivalent to 4 moles of silicon atoms.
[0053] In the silica particle forming process, the temperature of liquid (A), liquid (B), and their mixture is not particularly limited, for example, it is 5°C or higher and 100°C or lower, preferably 5°C or higher and 70°C or lower. The temperatures of liquid (A), liquid (B), and their mixture are preferably the same.
[0054] In the silica particle formation process, there are no particular restrictions on the pressure conditions during mixing; any conditions can be applied, including reduced pressure, normal pressure, and pressurized pressure. From a production cost perspective, normal pressure is preferred.
[0055] In one embodiment, the molar ratio of tetramethoxysilane or the like to the alkaline catalyst in the mixture at the end of the silica particle forming step is, for example, 0.10 or more and 0.80 or less, preferably 0.15 or more and 0.70 or less, more preferably 0.20 or more and 0.60 or less, and even more preferably 0.25 or more and 0.55 or less. That is, in one embodiment, the silica particle forming step includes mixing a liquid (B) such that the molar ratio of tetramethoxysilane or the like to the alkaline catalyst contained in the liquid (A) is within the above-mentioned range. The molar ratio of tetramethoxysilane or the like to the alkaline catalyst in the mixture at the end of the silica particle forming step is a value calculated from the amount of alkaline catalyst and tetramethoxysilane or the like added.
[0056] In one embodiment, the silica particle forming process may further include mixing a liquid (C) containing water into at least one of a liquid (A) and a mixed liquid (a mixture of liquid (B) in liquid (A)). Liquid (C) may be continuously or intermittently mixed into liquid (A) together with liquid (B), or continuously or intermittently mixed into a mixture in which liquid (B) is mixed in liquid (A).
[0057] One embodiment of the method for manufacturing silica sol of this manner includes: continuously or intermittently mixing liquid (B) and liquid (C) containing water into liquid (A), wherein liquid (A) contains an alkaline catalyst, water and a first organic solvent, and liquid (B) contains at least one of tetramethoxysilane and its condensate, and a second organic solvent, wherein the mixing includes: increasing the conductivity of the mixture after silica particles are formed in the mixture.
[0058] One embodiment of the method for manufacturing silica sol of this manner includes: continuously or intermittently mixing liquid (B) and liquid (C) containing water into liquid (A), forming silica particles in the mixture, wherein liquid (A) contains an alkaline catalyst, water and a first organic solvent, and liquid (B) contains at least one of tetramethoxysilane and its condensate, and a second organic solvent (silica particle formation step); increasing the conductivity of the mixture after the silica particle formation step (conductivity increase step); and continuously or intermittently mixing liquid (B) and liquid (C) in the mixture after the conductivity increase step, causing the silica particles in the mixture to bond and grow (silica particle growth step).
[0059] The liquid (C) in this embodiment contains water. The liquid (C) may contain other components without impairing the effects of the present invention.
[0060] In a preferred embodiment, the liquid (C) is composed of water. By making the liquid (C) composed of water, impurities contained in the mixture can be greatly reduced. Therefore, when the silica sol obtained by this manufacturing method is used as a polishing slurry, the influence of impurities on polishing can be suppressed. In addition, it can also be used for polishing objects that are sensitive to metallic impurities, such as silicon wafers and device wafers, and can provide a polishing slurry that can be applied in a wide range of applications.
[0061] From the viewpoint of minimizing the introduction of metal impurities, etc., the water contained in the liquid (C) is preferably pure water or ultrapure water.
[0062] The water content in the liquid (C) is preferably 95% by mass or more, more preferably 98% by mass or more, even more preferably 99% by mass or more, and particularly preferably 100% by mass.
[0063] In one embodiment, the liquid (C) comprises water and does not contain an alkaline catalyst.
[0064] When mixing liquid (B) and liquid (C) in at least one of liquid (A) and a mixture (a mixture in which liquid (B) is mixed), there are no particular restrictions on the method of adding liquid (B) and liquid (C). Approximately fixed amounts of each can be added simultaneously to at least one of liquid (A) and the mixture, or liquid (B) and liquid (C) can be added alternately to at least one of liquid (A) and the mixture. Liquid (B) and liquid (C) can be added randomly. From the viewpoint of suppressing changes in the amount of water used in the synthesis reaction, it is preferable to use the method of simultaneously adding liquid (B) and liquid (C) to at least one of liquid (A) and the mixture, and more preferably to use the method of simultaneously adding fixed amounts of each to at least one of liquid (A) and the mixture.
[0065] From the viewpoint of being able to suppress the local increase in the concentration of the alkaline catalyst, the method of adding liquid (B) and liquid (C) to at least one of liquid (A) and the mixture is preferably a method of continuously mixing liquid (B) and liquid (C) in at least one of liquid (A) and the mixture, or a method of intermittent mixing (e.g., dropwise addition).
[0066] When adding liquids (B) and (C) to at least one of liquids (A) and the mixture and mixing, the addition rates of liquids (B) and (C) are not particularly limited and can be appropriately adjusted within a range that does not produce a gel-like substance. The addition rate of liquid (B) can be set to the same rate as described above. Relative to 1 mol (converted to silicon atoms) of tetramethoxysilane and its condensate added to liquid (B), the addition rate of liquid (C) is, for example, 1 mol / min or more and 3 mol / min or less, preferably 2 mol / min, converted to water.
[0067] In the silica particle forming process, the temperature of liquid (A), liquid (B), liquid (C), and their mixture is not particularly limited, for example, it is between 5°C and 100°C, preferably between 5°C and 70°C. The temperatures of liquid (A), liquid (B), liquid (C), and their mixture are preferably the same.
[0068] As described above, a mixture containing silica particles can be obtained. After confirming the formation of silica particles in the mixture, the conductivity increase process can be initiated at any time. Examples of such "any time" include: the moment when the complete addition of liquid (B) and the required amount of liquid (C) to liquid (A) is finished, and the moment when the average secondary particle size of the silica particles in the mixture reaches the desired value. The formation of silica particles in the mixture can be confirmed using conventionally known methods. The formation of silica particles in the mixture can be confirmed, for example, by observation using a scanning electron microscope (SEM) or by measurement of the average secondary particle size using dynamic light scattering methods such as laser diffraction scattering.
[0069] (Conductivity increase process)
[0070] In the conductivity-increasing process, the conductivity of the mixture obtained in the silica particle formation process is increased.
[0071] In one embodiment, the average secondary particle size of the silica particles that causes the conductivity of the mixture to increase is 5 nm or more and 300 nm or less, preferably 5 nm or more and 100 nm or less, more preferably 5 nm or more and 50 nm or less, and even more preferably 10 nm or more and 30 nm or less. The average secondary particle size of the silica particles can be determined, for example, by dynamic light scattering methods such as laser diffraction scattering. More specifically, the average secondary particle size of the silica particles is a value determined by the method described in the examples.
[0072] In one embodiment, the average longest diameter of the primary particles of silica particles that increases the conductivity of the mixture is 2 nm or more and 50 nm or less, preferably 5 nm or more and 40 nm or less, and more preferably 10 nm or more and 30 nm or less. The average longest diameter of the primary particles of silica particles refers to, for example... Figure 1 As illustrated by the double arrows, the longest diameter of the primary particles of silica is measured, and the average of the longest diameters of all measured primary particles of silica is calculated. The longest diameter of the primary particles of silica can be determined, for example, by observation using a scanning electron microscope (SEM). Specifically, the average of the longest diameters of the primary particles of silica is the value determined by the method described in the examples.
[0073] In one embodiment, the molar ratio of tetramethoxysilane or the like to the base catalyst in the mixture at the start of the conductivity-increasing step is, for example, 0.10 or more and 0.80 or less, preferably 0.15 or more and 0.70 or less, more preferably 0.20 or more and 0.60 or less, and even more preferably 0.25 or more and 0.55 or less. The molar ratio of tetramethoxysilane or the like to the base catalyst in the mixture at the start of the conductivity-increasing step is a value calculated from the amount of base catalyst and tetramethoxysilane or the like added in the silica particle forming step.
[0074] After the silica particles are formed in the mixture, the conductivity enhancement process can begin at any time, as described above, and can end at the moment when the conductivity of the mixture after the silica particle formation process reaches the desired value (the moment when the rate of increase of the conductivity of the mixture reaches the desired value) (proceeding into the next silica particle growth process). The conductivity of the mixture can be measured using the method described in the examples.
[0075] In the conductivity-increasing process, from the viewpoint of further enhancing the effects of the present invention, the rate of increase in the conductivity of the mixture after the silica particle formation process is preferably 110% or more. There is no particular upper limit to this rate of increase, for example, it is 160% or less, preferably 140% or less. The rate of increase in conductivity (%) is calculated by dividing the conductivity of the mixture at the end of the conductivity-increasing process by the conductivity of the mixture at the beginning of the conductivity-increasing process, multiplied by 100.
[0076] One method to increase the conductivity of the mixture after the silica particle formation process is to increase the amount of ions from the alkaline catalyst in the mixture. In one embodiment, the increase in conductivity of the mixture after the silica particle formation process is achieved by increasing the amount of ions from the alkaline catalyst in the mixture (increasing the ion concentration from the alkaline catalyst).
[0077] Methods for increasing the amount of ions from the alkaline catalyst in the mixture include: lowering the temperature of the mixture after the silica particle formation process; and adding a liquid (D) containing ammonia to the mixture.
[0078] In a preferred embodiment, the increase in the conductivity of the mixture after the silica particle formation process is achieved by lowering the temperature of the mixture.
[0079] The alkaline catalyst in the mixture dissociates itself in water or causes water to dissociate, producing hydroxide ions. For example, when ammonia (NH3) is used as the alkaline catalyst, ammonia in water exhibits an equilibrium state as shown in the following formula.
[0080] [Chemical Formula 1]
[0081]
[0082] By lowering the temperature of the mixture, the alkaline catalyst (e.g., ammonia) in the mixture dissociates on its own in the water, or causes the water to dissociate, thus increasing the ion content. The ion content in the mixture is related to the conductivity of the mixture; therefore, increasing the ion content can increase the conductivity of the mixture.
[0083] In this specification, "ions from alkaline catalysts" includes ions generated by the self-dissociation of the alkaline catalyst in water, as well as ions generated by the alkaline catalyst causing water to dissociate.
[0084] When the temperature of the mixture is reduced, the temperature obtained by subtracting the temperature of the mixture at the end of the conductivity increase process from the temperature of the mixture at the beginning of the conductivity increase process is, for example, 5°C or more, preferably 10°C or more, more preferably 15°C or more, and even more preferably 20°C or more.
[0085] When lowering the temperature of the mixture, the temperature can be lowered continuously or in stages, preferably continuously.
[0086] There are no particular limitations on the method for lowering the temperature of the mixture; examples include cooling the reaction vessel containing the mixture to the desired temperature. When cooling the mixture, stirring is also acceptable. There are no particular limitations on the stirring speed, for example, it can be 30 rpm or higher and 500 rpm or lower.
[0087] When lowering the temperature of the mixture, there is no particular limitation on the time required to lower the mixture to the desired temperature, and it can be adjusted appropriately. For example, the time required to lower the mixture to the desired temperature can be 90 minutes or more.
[0088] In a preferred embodiment, the increase in the conductivity of the mixture after the silica particle formation process is achieved by adding an ammonia-containing liquid (D) to the mixture. By adding the ammonia-containing liquid (D) to the mixture, the ammonia added to the mixture dissociates on its own in the water, or causes the water to dissociate, thereby increasing the ion content. This, in turn, increases the conductivity of the mixture.
[0089] Liquid (D) preferably contains water in addition to ammonia. From the viewpoint of minimizing the introduction of metal impurities, etc., the water contained in liquid (D) is preferably pure water or ultrapure water. In addition to ammonia and water, liquid (D) may also contain other components without impairing the effects of the present invention. In one embodiment, liquid (D) is composed of ammonia and water.
[0090] There is no particular limitation on the ammonia content in the liquid (D), but it is, for example, more than 1% by mass and less than 30% by mass relative to the total amount of liquid (D) (100% by mass).
[0091] There is no particular limitation on the water content in the liquid (D), but it is, for example, more than 70% by mass and less than 99% by mass relative to the total amount of liquid (D) (100% by mass).
[0092] There are no particular limitations on the method of adding ammonia-containing liquid (D) to the mixture after the silica particle forming process. Liquid (D) can be added to the mixture all at once, or continuously or intermittently. Liquid (D) can be added to the mixture more than twice. In one embodiment, the increase in the conductivity of the mixture after the silica particle forming process is achieved by adding ammonia-containing liquid (D) to the mixture all at once.
[0093] There is no particular limitation on the amount of liquid (D) containing ammonia added; it can be set to the amount that achieves the rate of increase in the conductivity value of the mixture after the desired silica particle formation process.
[0094] The increase in the conductivity of the mixture after the silica particle forming process can be achieved by combining a combination of lowering the temperature of the mixture after the silica particle forming process and adding a liquid (D) containing ammonia to the mixture after the silica particle forming process.
[0095] In the conductivity-increasing process, the mixture may consist only of liquid (B), only of liquid (C), or both liquid (B) and liquid (C). The mixing of liquid (B) and liquid (C) relative to the mixture may also be stopped (interrupted). When liquid (B) is mixed in the mixture, it is preferable to minimize the amount of liquid (B) added. In this case, the addition rate of liquid (B) relative to 1 mol of water contained in liquid (A) can be set to less than 8.5 × 10⁻⁶ silicon atoms. -4 mol / min. If liquid (C) contains ammonia, liquid (C) can be used as liquid (D). When mixing liquid (C) in a mixture (except where liquid (C) contains ammonia), it is preferable to minimize the amount of liquid (C) added. In a preferred embodiment, during the conductivity increase step, from the viewpoint of increasing the amount of ions from the alkaline catalyst in the mixture (increasing the ion concentration from the alkaline catalyst), mixing liquid (B), or liquid (B) and liquid (C) in the mixture is stopped (interrupted).
[0096] In the conductivity enhancement process, if the mixed solution contains only mixed solution (B), only mixed solution (C), or both mixed solution (B) and liquid (C), the composition of liquid (B) in the silica particle growth process can be the same as or different from that in the conductivity enhancement process. Similarly, the composition of liquid (C) in the silica particle growth process can be the same as or different from that in the conductivity enhancement process.
[0097] As described above, it is possible to obtain a mixture that increases the conductivity value.
[0098] (Silica particle growth process)
[0099] In the silica particle growth process, a liquid (B) containing at least one of tetramethoxysilane and its condensate, and a second organic solvent, is continuously or intermittently mixed into the mixture obtained in the conductivity increasing process, causing the silica particles in the mixture to bond and grow. Compared to the mixture obtained in the silica particle forming process, the amount of ions from the alkaline catalyst (e.g., ammonia) is increased in the mixture obtained in the conductivity increasing process. By mixing the mixture (B) in a state with increased ion content, the silica particles readily bond together via hydrolyzed tetramethoxysilanes, etc. Thus, a mixture containing silica particles with a high aspect ratio can be obtained.
[0100] The silica particle growth process begins by adding liquid (B) to the mixture and ends by completing the addition of liquid (B). For example, the silica particle growth process can be completed by adding all of the liquid (B), or it can be completed when the mixture containing silica particles with the desired average aspect ratio is obtained. The silica particle growth process can be performed in two or more steps.
[0101] By performing a silica particle growth process, the concentration (content) of silica particles in the mixture can be increased. The lower limit of the concentration (content) of silica particles in the mixture obtained in the silica particle growth process, relative to the total mass of the mixture, is, for example, 4% by mass or more, preferably 5% by mass or more, more preferably 7% by mass or more, further preferably 8% by mass or more, and particularly preferably 9% by mass or more. By performing the silica particle growth process two or more times, the concentration (content) of silica particles in the mixture can be further increased. The upper limit of the concentration (content) of silica particles in the mixture is not particularly limited as long as gelation does not occur. The upper limit of the concentration (content) of silica particles in the mixture can be 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, or 20% by mass or less. The concentration (content) of silica particles in the mixture can be 4% or more by mass and less than 40% by mass, 5% or more by mass and less than 35% by mass, 7% or more by mass and less than 30% by mass, 8% or more by mass and less than 25% by mass, or 9% or more by mass and less than 20% by mass.
[0102] In one embodiment, the silica particle growth step may further include: mixing a water-containing liquid (C) into the mixture obtained in the conductivity-increasing step. That is, one embodiment of the method for manufacturing silica sol of this manner includes: continuously or intermittently mixing a liquid (B) into a liquid (A) (mixing step), the mixing (mixing step) including: increasing the conductivity value of the mixture after forming silica particles in the mixture, and the mixing (mixing step) further including: mixing a water-containing liquid (C) into at least one of the liquid (A) and the mixture.
[0103] The descriptions of liquids (B) and (C) in the silica particle growth process are as described in the silica particle formation process above. The composition of liquid (B) in the silica particle growth process may be the same as or different from that in the silica particle growth process. Similarly, the composition of liquid (C) in the silica particle growth process may be the same as or different from that in the silica particle growth process.
[0104] In the silica particle growth process, stirring the mixture is preferred. There are no particular limitations on the stirring speed, for example, it can be above 30 rpm and below 500 rpm.
[0105] In the silica particle growth process, the addition rate of liquid (B) is not particularly limited and can be adjusted appropriately within a range that does not produce a gel-like substance. For example, relative to 1 mol of water contained in liquid (A), the addition rate of liquid (B), converted to silicon atoms, can be set to 8.5 × 10⁻⁶. -4 mol / min or higher and 5.6 × 10-3 Below mol / min.
[0106] The addition rate of liquid (B) can be the same as or different from the addition rate of liquid (B) in the silica particle formation process. From the viewpoint of shortening the manufacturing time of silica sol, the addition rate of liquid (B) can be more than twice that of liquid (B) in the silica particle formation process.
[0107] In the silica particle growth process, there are no particular restrictions on the addition rates of liquid (B) and liquid (C) when adding and mixing the mixture. These rates can be adjusted appropriately within a range that does not produce a gel-like substance. The addition rate of liquid (B) can be set to the same rate as described above. Relative to 1 mol (converted to silicon atoms) of tetramethoxysilane and its condensate added to liquid (B), the addition rate of liquid (C), for example, converted to water, should be 1 mol / min or more and 3 mol / min or less, preferably 2 mol / min.
[0108] When performing more than two silica particle growth processes, the composition of liquid (B) and liquid (C) used in each process, the addition rate of liquid (B) and liquid (C) in each process, and the temperature of liquid (B), liquid (C) and mixture in each process can be the same or different.
[0109] As described above, it is possible to obtain a mixture containing more silica particles with a high aspect ratio.
[0110] In this manufacturing method, the mixture obtained in the silica particle growth process can be used directly as a silica sol. The mixture obtained in the silica particle growth process can be subjected to subsequent processes, as described later. In a preferred embodiment, from the viewpoint of suppressing the aggregation of silica particles, a water replacement process is performed to replace the organic solvent present in the mixture obtained in the silica particle growth process with water.
[0111] (Subsequent processes)
[0112] In the method for manufacturing silica sol in this manner, after the silica particle growth process, the following subsequent processes can be performed.
[0113] Specifically, at least one of the following steps can be performed: a water replacement step in which the organic solvent present in the mixture obtained in the silica particle growth step is replaced with water; and a concentration step in which the mixture obtained in the silica particle growth step is concentrated. More specifically, a concentration step in which only the mixture obtained in the silica particle growth step is concentrated can be performed, or a water replacement step in which only the organic solvent in the mixture obtained in the silica particle growth step is replaced with water can be performed, or a water replacement step in which the organic solvent in the mixture after the concentration step is replaced with water can be performed, or a concentration step in which the mixture after the water replacement step is concentrated can be performed. Furthermore, multiple concentration steps can be performed, in which case a water replacement step can be performed between concentration steps. For example, a water replacement step in which the organic solvent in the concentrated liquid is replaced with water can be performed after the concentration step, followed by a concentration step in which the liquid after water replacement is concentrated.
[0114] (Water replacement process)
[0115] As one embodiment, the method for manufacturing silica sol in this manner may include a step of replacing the organic solvent contained in the mixture obtained in the silica particle growth process with water (hereinafter also referred to as the "water replacement step"). The mixture used in this embodiment also includes a method of concentrating the mixture obtained in the silica particle growth process.
[0116] By replacing the organic solvent in the mixture obtained in the silica particle growth process with water, and by selecting ammonia as the alkaline catalyst, the pH of the manufactured silica sol can be adjusted to the neutral region. Furthermore, by removing unreacted substances contained in the mixture obtained in the silica particle growth process, a long-term stable silica sol can be obtained.
[0117] The method for replacing the organic solvent in the mixture obtained in the silica particle growth process with water can be a conventionally known method. For example, one method involves maintaining the volume of the mixture obtained in the silica particle growth process at a certain level while adding water dropwise and performing the replacement by heating and distillation. In this case, the replacement operation is preferably carried out until the liquid temperature and the temperature at the top of the column reach the boiling point of the water being replaced.
[0118] From the viewpoint of minimizing the introduction of metal impurities, etc., pure water or ultrapure water is preferred to be used in this process.
[0119] As a method for replacing the organic solvent in the mixture obtained in the silica particle growth process with water, the following method can also be listed: the mixture obtained in the silica particle growth process is separated by centrifugation and then redispersed in water.
[0120] (Concentration process)
[0121] As one embodiment, the method for manufacturing silica sol in this manner may include a step of further concentrating the mixture obtained in the silica particle growth process (hereinafter referred to as the "concentration step"). It should be noted that the mixture used in this embodiment also includes the mixture obtained in the silica particle growth process that has undergone water replacement.
[0122] There are no particular restrictions on the method for concentrating the mixture obtained in the silica particle growth process. Commonly known methods can be used, such as heating concentration and membrane concentration.
[0123] In the heating concentration method, a concentrated mixture can be obtained by heating and concentrating the mixture obtained in the silica particle growth process under normal pressure or reduced pressure.
[0124] In membrane concentration methods, for example, silica sol obtained during the silica particle growth process can be concentrated through membrane separation based on ultrafiltration, which is capable of filtering silica particles. There are no particular limitations on the molecular weight cutoff of the ultrafiltration membrane; the molecular weight cutoff can be selected based on the particle size produced. There are no particular limitations on the material constituting the ultrafiltration membrane; examples include polysulfone, polyacrylonitrile, sintered metals, ceramics, and carbon. There are no particular limitations on the shape of the ultrafiltration membrane; examples include spiral, tubular, and hollow fiber types. In ultrafiltration, there are no particular limitations on the operating pressure; it can be set below the operating pressure of the ultrafiltration membrane used.
[0125] In the manufacture of the silica sol of this method, the physical properties of the silica particles in the manufactured silica sol will be described later in the section on silica sol of another aspect of the present invention.
[0126] <Silica sol>
[0127] Another aspect of the present invention relates to a silica sol comprising silica particles having an average aspect ratio of 1.50 or higher, wherein the number of silica particles having an aspect ratio of 1.50 or higher accounts for 40% or more of the total number of silica particles, and the concentration of silica particles is 4% by mass or higher. The silica particles contained in the silica sol of this embodiment have a high average aspect ratio, thus improving grinding performance, for example, reducing haze.
[0128] The silica sol of this method can be obtained by the silica sol manufacturing method described above. From the viewpoint of achieving high purity of the silica sol, the silica sol of this method is preferably a silica sol manufactured using the sol-gel method. In a preferred embodiment, the silica sol of this method is a silica sol obtained by the silica sol manufacturing method described above using the sol-gel method.
[0129] In this specification, the aspect ratio refers to the value obtained by measuring the values of the long side and the short side of the smallest rectangle circumscribed with the silica particle, and calculating the ratio of the long side value to the short side value (long side value / short side value). The average aspect ratio refers to the value obtained by calculating the average aspect ratio of a specified number (e.g., more than 100) of silica particles. The aspect ratio and average aspect ratio can be determined, for example, by observation using a scanning electron microscope (SEM). More specifically, the aspect ratio and average aspect ratio are values measured using the methods described in the examples.
[0130] The ratio of the number of silica particles with an aspect ratio of 1.50 or greater to the total number of silica particles can be determined by observing the silica particles in the SEM image (e.g., 100 or more) using a scanning electron microscope (SEM). The ratio (%) of the number of silica particles with an aspect ratio of 1.50 or greater in the SEM image to the total number of silica particles in the SEM image is calculated as follows: (Number of silica particles with an aspect ratio of 1.50 or greater in the SEM image / Total number of silica particles in the SEM image × 100). Details of the measurement method are described in the examples.
[0131] In this type of silica sol, the lower limit of the average aspect ratio of the silica particles is 1.50 or more. The upper limit of the average aspect ratio of the silica particles is, for example, 5.00 or less, preferably 4.00 or less, and more preferably 3.00 or less. The upper limit of the average aspect ratio of the silica particles can be 2.00 or less, 1.80 or less, or 1.65 or less. The average aspect ratio of the silica particles is preferably 1.50 or more and 5.00 or less, more preferably 1.50 or more and 4.00 or less, and more preferably 1.50 or more and 3.00 or less. The average aspect ratio of the silica particles can be 1.50 or more and 2.00 or less, 1.50 or more and 1.80 or less, or 1.50 or more and 1.65 or less.
[0132] In this type of silica sol, the lower limit of the ratio of the number of silica particles with an aspect ratio of 1.50 or higher to the total number of silica particles is 40% or higher, preferably 50% or higher. There is no particular limit to the upper limit of the ratio of the number of silica particles with an aspect ratio of 1.50 or higher to the total number of silica particles; for example, it can be 80% or lower, 70% or lower, or 60% or lower. The ratio of the number of silica particles with an aspect ratio of 1.50 or higher to the total number of silica particles is, for example, 40% or higher and 80% or lower. The ratio of the number of silica particles with an aspect ratio of 1.50 or higher to the total number of silica particles can be 50% or higher and 70% or lower, or 50% or higher and 60% or lower.
[0133] In the silica sol of this method, the ratio of the number of silica particles with a sphericity of 0.90 or higher to the total number of silica particles is preferably 40% or less.
[0134] A preferred embodiment of the present invention relates to a silica sol comprising silica particles having an average aspect ratio of 1.50 or more, wherein the number of silica particles having an aspect ratio of 1.50 or more accounts for 40% or more of the total number of silica particles, the number of silica particles having a sphericity of 0.90 or more accounts for 40% or less of the total number of silica particles, and the concentration of silica particles is 4% by mass or more.
[0135] The ratio of the number of silica particles with a sphericity of 0.90 or higher to the total number of silica particles can be determined as follows: Scanning electron microscopy (SEM) is performed to observe the silica particles in the SEM image, and the sphericity of each particle is measured. The ratio (%) of the number of silica particles with a sphericity of 0.90 or higher in the SEM image to the total number of silica particles in the SEM image (e.g., 100 or more) is calculated (= number of silica particles with a sphericity of 0.90 or higher in the SEM image / total number of silica particles in the SEM image × 100). Details of the measurement method are described in the examples.
[0136] In the silica sol of this method, the upper limit of the ratio of the number of silica particles with a sphericity of 0.90 or higher to the total number of silica particles is preferably 30% or less. The lower limit of the ratio of the number of silica particles with a sphericity of 0.90 or higher to the total number of silica particles is not particularly limited, and can be, for example, 5% or more or 10% or more. The ratio of the number of silica particles with a sphericity of 0.90 or higher to the total number of silica particles is preferably 5% or more and 40% or less, more preferably 10% or more and 30% or less.
[0137] In this type of silica sol, the average sphericity of the silica particles is preferably 0.80 or less. A preferred embodiment of the present invention relates to a silica sol comprising silica particles having an average aspect ratio of 1.50 or more, wherein the number of silica particles having an aspect ratio of 1.50 or more accounts for 40% or more of the total number of silica particles, the number of silica particles with a sphericity of 0.90 or more accounts for 40% or less of the total number of silica particles, the average sphericity of the silica particles is 0.80 or less, and the concentration of silica particles is 4% by mass or more.
[0138] In this specification, average roundness refers to the value obtained by calculating the average roundness of all silica particles contained in the silica sol. The average roundness is a value measured using the method described in the examples.
[0139] The upper limit of the average sphericity of the silica particles is more preferably 0.75 or less. The lower limit of the average sphericity of the silica particles is not particularly limited, and can be, for example, 0.30 or more, 0.40 or more, or 0.50 or more. The average sphericity of the silica particles is preferably 0.30 or more and 0.80 or less, more preferably 0.40 or more and 0.75 or less, and even more preferably 0.50 or more and 0.75 or less.
[0140] In this type of silica sol, the lower limit of the average primary particle size of the silica particles is not particularly limited, but is, for example, 5 nm or more, preferably 10 nm or more, and more preferably 20 nm or more. The upper limit of the average primary particle size of the silica particles is not particularly limited, but is, for example, 150 nm or less, preferably 100 nm or less, and more preferably 50 nm or less. The average primary particle size of the silica particles can be 5 nm or more and 150 nm or less, 10 nm or more and 100 nm or less, or 20 nm or more and 50 nm or less. The average primary particle size of the silica particles can be calculated, for example, based on the specific surface area (SA) and density of the silica particles calculated by the BET method. More specifically, the average primary particle size of the silica particles is a value measured by the method described in the examples.
[0141] In the silica sol of this method, the average secondary particle size of the silica particles is, for example, 5 nm or more and 300 nm or less, preferably 20 nm or more and 150 nm or less. The average secondary particle size of the silica particles can be determined, for example, by dynamic light scattering methods such as laser diffraction scattering. More specifically, the average secondary particle size of the silica particles is the value determined by the method described in the examples.
[0142] In the silica sol of this method, the average degree of association of silica particles (the ratio of average secondary particle size to average primary particle size) is, for example, 1.0 or more, preferably 1.0 or more and 10 or less, more preferably 1.3 or more and 7.0 or less, and even more preferably 1.5 or more and 5.0 or less.
[0143] In this type of silica sol, the concentration (content) of silica particles is 4% by mass or more relative to the total mass of the silica sol. The lower limit of the concentration (content) of silica particles relative to the total mass of the silica sol is preferably 5% by mass or more, more preferably 7% by mass or more, further preferably 8% by mass or more, and particularly preferably 9% by mass or more. The silica sol of this type, manufactured by the above-described silica sol manufacturing method, can contain 4% by mass or more of silica particles even without the above-described concentration step. The upper limit of the concentration (content) of silica particles is not particularly limited as long as gelation does not occur. The upper limit of the concentration (content) of silica particles in the mixture can be 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, or 20% by mass or less. The concentration (content) of silica particles can be 4% or more by mass and less than 40% by mass, 5% or more by mass and less than 35% by mass, 7% or more by mass and less than 30% by mass, 8% or more by mass and less than 25% by mass, or 9% or more by mass and less than 20% by mass.
[0144] The pH of the silica sol produced by this method is not particularly limited as long as gelation does not occur. For example, the pH of the silica sol obtained by the above manufacturing method can be 5.0 or higher and 8.0 or lower, or 6.5 or higher and 7.5 or lower. The pH of the silica sol can be measured using a pH meter.
[0145] The silica sol produced in this method may contain water. There are no particular limitations on the concentration (content) of water in the silica sol; it can be adjusted appropriately based on the concentration (content) of the silica particles.
[0146] Other than water, components that may be included in the silica sol can be derived from the aforementioned manufacturing process. Examples of components other than water include alkaline catalysts, organic solvents, tetramethoxysilanes and their condensates, and metallic impurities. Components other than silica particles and water are preferably removed as much as possible. The content of components other than silica particles and water in the silica sol is preferably 0.0001% by mass or less, more preferably 0% by mass. As described above, from the viewpoint of high purity, the silica sol of this method is preferably a silica sol manufactured using the sol-gel method.
[0147] <Application>
[0148] The silica sol produced by this method can be used in a variety of applications. In particular, it is suitable as an abrasive for grinding objects such as semiconductor substrates. Examples of grinding objects include, for instance, metals or semi-metals such as silicon, aluminum, nickel, tungsten, steel, tantalum, titanium, and stainless steel, or their alloys; glassy materials such as quartz glass, aluminosilicate glass, and glassy carbon; ceramic materials such as alumina, silica, sapphire, silicon nitride, tantalum nitride, and titanium carbide; compound semiconductor substrate materials such as silicon carbide, gallium nitride, and gallium arsenide; resin materials such as polyimide resin; and so on. Furthermore, the silica sol produced by the manufacturing method of this invention can be used as a resin filler (e.g., a sealant for semiconductor components), a hardening agent, a resin modifier, a surface treatment agent, a coating, a pigment, a catalyst, an anti-slip agent, a spacer for liquid crystal display devices, a fiber treatment agent, a binder, an adhesive, a polymer coagulant, a toner, a cleaning agent, cosmetics, dental materials, nanocomposite materials, thermal recorders, photosensitive films, and precipitants.
[0149] The present invention includes the following methods and implementation methods.
[0150] [1] A method for manufacturing silica sol, comprising: continuously or intermittently mixing liquid (B) into liquid (A), said liquid (A) comprising an alkaline catalyst, water and a first organic solvent, said liquid (B) comprising at least one of tetramethoxysilane and its condensate, and a second organic solvent.
[0151] The mixing process includes: increasing the electrical conductivity of the mixture after forming silica particles in the mixture.
[0152] [2] According to the manufacturing method described in [1] above, the increase in the conductivity of the mixture is achieved by increasing the amount of ions from the alkaline catalyst in the mixture.
[0153] [3] According to the manufacturing method described in [1] or [2] above, the increase in the conductivity value of the mixture is achieved by reducing the temperature of the mixture.
[0154] [4] The manufacturing method according to any one of [1] to [3] above, wherein the increase in the conductivity value of the mixture is achieved by adding a liquid (D) containing ammonia to the mixture.
[0155] [5] The manufacturing method according to any one of [1] to [4] above, wherein the mixing further includes mixing a liquid (C) containing water into at least one of the liquid (A) and the mixture.
[0156] [6] The manufacturing method according to any one of [1] to [5] above, wherein the rate of increase of the conductivity value of the mixture is 110% or more.
[0157] [7] The manufacturing method according to any one of [1] to [6] above, wherein the average secondary particle size of the silica particles when the conductivity of the mixture increases is 5 nm or more and 300 nm or less.
[0158] [8] A silica sol comprising silica particles having an average aspect ratio of 1.50 or more, wherein the number of silica particles having an aspect ratio of 1.50 or more is 40% or more relative to the total number of silica particles, and the concentration of the silica particles is 4% by mass or more.
[0159] [9] According to the silica sol described in [8] above, the number of silica particles with a sphericity of 0.90 or higher is 40% or less relative to the total number of silica particles.
[0160] Example
[0161] The present invention will be further described in detail using the following examples and comparative examples. However, the scope of the present invention is not limited to the following examples. It should be noted that, unless otherwise specified, "%" and "parts" refer to "mass %" and "parts by mass," respectively. Furthermore, in the following examples, unless otherwise specified, the operation is carried out at room temperature (20~25°C) and relative humidity 40~50%RH.
[0162] <Methods for determining various physical properties>
[0163] In the examples and comparative examples, various physical properties were determined by the following methods.
[0164] (Scanning electron microscope (SEM) image)
[0165] For silica particles in the mixture and silica sol, a scanning electron microscope (SEM) SU8000 (manufactured by Hitachi High Technology Co., Ltd.) was used to capture SEM images at a magnification of 100 to 1000 particles.
[0166] (Average length of the longest diameter of primary silica particles)
[0167] In the mixture, for all silica particles in the captured SEM images, such as Figure 1 As illustrated by the double arrows, the longest diameter of the primary particles of each silica particle is determined, and the average value of the longest diameter of the primary particles of the silica particles is calculated.
[0168] (Average primary particle size)
[0169] The average primary particle size of silica particles in the silica sol was based on the specific surface area (SA) of silica particles measured using the BET method with a Macsorb (registered trademark) HM Model-1201 (manufactured by Mountech Co., Ltd.), a fully automated specific surface area measuring device. The true specific gravity of silica was set to 2.2 g / cm³. 3 The value is calculated using the formula: particle size = 6000 / (SA×2.2).
[0170] (Average secondary particle size)
[0171] The average secondary particle size of silica particles in the mixture and silica sol was determined as the volume average particle size using dynamic light scattering method with a particle size distribution measuring device (UPA-UT151, manufactured by Nikkiso Co., Ltd.).
[0172] (Conductivity)
[0173] Regarding the conductivity of the mixture, a portable conductivity meter D-210C (manufactured by Horiba Manufacturing Co., Ltd.) was used, and the electrode of the device was immersed in the mixture for measurement.
[0174] (Average aspect ratio)
[0175] For silica particles in silica sol, the values of the long side and short side of the smallest rectangle circumscribed by each silica particle in the captured SEM image are measured. The ratio of the calculated long side value to the short side value (long side value / short side value) is taken as the aspect ratio, and the average aspect ratio of all silica particles in the captured SEM image is calculated.
[0176] (The ratio of the number of silica particles with an aspect ratio of 1.50 or greater to the total number of silica particles)
[0177] For silica particles in silica sol, the values of the long and short sides of the smallest rectangle circumscribed by each silica particle in the captured SEM image are measured. The ratio of the calculated long side value to the short side value (long side value / short side value) is taken as the aspect ratio. The percentage (%) of the number of silica particles with an aspect ratio of 1.50 or higher in the SEM image relative to the total number of silica particles in the SEM image is calculated (= number of silica particles with an aspect ratio of 1.50 or higher in the SEM image / total number of silica particles in the SEM image × 100).
[0178] (Average roundness)
[0179] For silica particles in silica sol, the roundness of each silica particle in the captured SEM image is measured, and the average roundness of all silica particles in the captured SEM image is calculated.
[0180] To determine the roundness of the silica particles, calculate the area (S) and perimeter (L) using the following formula: Roundness = 4πS / L 2 (S = area of circle, L = circumference).
[0181] (The ratio of the number of silica particles with a sphericity of 0.90 or higher to the total number of silica particles)
[0182] For silica particles in silica sol, the roundness of each silica particle in the captured SEM image was measured. The percentage (%) of the number of silica particles with a roundness of 0.90 or higher in the SEM image relative to the total number of silica particles in the SEM image was calculated (= number of silica particles with a roundness of 0.90 or higher in the SEM image / total number of silica particles in the SEM image × 100).
[0183] <Example 1>
[0184] (Silica particle formation process)
[0185] In a 3L reaction vessel equipped with a stirrer and a cooling function, a solution (A) containing 1296g of methanol (manufactured by Kanto Chemical Co., Ltd.) mixed with 65g of pure water and 116g of 29% ammonia was added. The temperature of the liquid in the reaction vessel (the temperature of the mixed solution) was maintained at 50°C. While stirring at 300 rpm, a solution (B) containing 88g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22g of methanol and a solution (C) containing 21g of pure water were added and mixed to prepare a mixed solution for the synthesis reaction.
[0186] The rate of addition of liquid (B) relative to 1 mol of water contained in liquid (A) is 1.4 × 10⁻⁶ in silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0187] The synthesis reaction was completed by adding the full amounts of liquids (B) and (C), resulting in a mixture containing silica particles. The presence of silica particles in the mixture was confirmed by measuring the average longest diameter and average secondary diameter of the primary silica particles, as well as the concentration of silica particles in the mixture. The average longest diameter of the primary silica particles was 21 nm. The average secondary diameter of the formed silica particles was 22 nm. The concentration of silica particles in the mixture was 2.2% by mass.
[0188] (Conductivity increase process)
[0189] The conductivity of the mixture obtained in the silica particle formation process was measured (the conductivity of the mixture at the start of the conductivity increase process). After measurement, the mixture was stirred at 300 rpm while being cooled to 30°C for 90 minutes to obtain a mixture with increased conductivity. The conductivity of the mixture was measured again at the point where the temperature reached 30°C (the conductivity of the mixture at the end of the conductivity increase process). The conductivity of the mixture at the end of the conductivity increase process increased by 128% compared to the start of cooling (= conductivity of the mixture at the end of the conductivity increase process / conductivity of the mixture at the start of the conductivity increase process × 100).
[0190] (Silica particle growth process 1)
[0191] For the mixture obtained in the conductivity increase process, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C, and while stirring at 300 rpm, liquid (B) containing 88 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22 g of methanol and liquid (C) containing 21 g of pure water are continuously added to allow the reaction to proceed.
[0192] The addition rate of liquid (B) was set relative to 1 mol of water contained in liquid (A), which is equivalent to 2.8 × 10⁻⁶ silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0193] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 4.0% by mass.
[0194] (Silica particle growth process 2)
[0195] For the mixture obtained in the silica particle growth process 1, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C. While stirring at 300 rpm, liquid (B) containing 379 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 95 g of methanol and liquid (C) containing 90 g of pure water are added continuously to carry out the reaction.
[0196] The addition rate of liquid (B) was set relative to 1 mol of water contained in liquid (A), which is equivalent to 3.5 × 10⁻⁶ silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0197] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 9.5% by mass.
[0198] (Water replacement process)
[0199] The mixture obtained in step 2 of the silica particle growth process is heated to a boiling point under normal pressure. During heating, pure water is added while maintaining a constant liquid level to induce distillation, thereby replacing the methanol with pure water to obtain silica sol.
[0200] <Example 2>
[0201] (Silica particle formation process)
[0202] In a 3L reaction vessel equipped with a stirrer and a cooling function, a solution (A) containing 1341g of methanol (manufactured by Kanto Chemical Co., Ltd.) mixed with 21g of pure water and 116g of 29% ammonia was added. The temperature of the liquid in the reaction vessel (the temperature of the mixed solution) was maintained at 50°C. While stirring at 300 rpm, a solution (B) containing 88g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22g of methanol and a solution (C) containing 21g of pure water were added and mixed to prepare a mixed solution for the synthesis reaction.
[0203] The rate of addition of liquid (B) relative to 1 mol of water contained in liquid (A) is 2.0 × 10⁻⁶ in silicon atoms. -3mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0204] The synthesis reaction was completed by adding the full amounts of liquids (B) and (C), resulting in a mixture containing silica particles. The presence of silica particles in the mixture was confirmed by measuring the average longest diameter and average secondary diameter of the primary silica particles, as well as the concentration of silica particles in the mixture. The average longest diameter of the primary silica particles was 16 nm. The average secondary diameter of the formed silica particles was 19 nm. The concentration of silica particles in the mixture was 2.2% by mass.
[0205] (Conductivity increase process)
[0206] The conductivity of the mixture obtained in the silica particle formation process was measured (the conductivity of the mixture at the start of the conductivity increase process). After measurement, the mixture was stirred at 300 rpm while being cooled to 30°C for 90 minutes to obtain a mixture with increased conductivity. The conductivity of the mixture was measured again at the point where the temperature reached 30°C (the conductivity of the mixture at the end of the conductivity increase process). The conductivity of the mixture at the end of the conductivity increase process increased by 134% compared to the start of cooling (= conductivity of the mixture at the end of the conductivity increase process / conductivity of the mixture at the start of the conductivity increase process × 100).
[0207] (Silica particle growth process 1)
[0208] For the mixture obtained in the conductivity increase process, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C, and while stirring at 300 rpm, liquid (B) containing 88 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22 g of methanol and liquid (C) containing 21 g of pure water are continuously added to carry out the synthesis reaction.
[0209] The addition rate of liquid (B) was set relative to 1 mol of water contained in liquid (A), which is equivalent to 4.0 × 10⁻⁶ silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0210] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 4.0% by mass.
[0211] (Silica particle growth process 2)
[0212] For the mixture obtained in the silica particle growth process 1, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C. While stirring at 300 rpm, liquid (B) containing 379 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 95 g of methanol and liquid (C) containing 90 g of pure water are added continuously to carry out the reaction.
[0213] The addition rate of liquid (B) was set relative to 1 mol of water contained in liquid (A), which is equivalent to 5.0 × 10⁻⁶ silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0214] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 9.5% by mass.
[0215] (Water replacement process)
[0216] The mixture obtained in step 2 of the silica particle growth process is heated to a boiling point under normal pressure. During heating, pure water is added while maintaining a constant liquid level to induce distillation, thereby replacing the methanol in the mixture with pure water to obtain silica sol.
[0217] <Example 3>
[0218] (Silica particle formation process)
[0219] In a 3L reaction vessel equipped with a stirrer and a cooling function, a solution (A) containing 1341g of methanol (manufactured by Kanto Chemical Co., Ltd.) mixed with 21g of pure water and 116g of 29% ammonia was added. The temperature of the liquid in the reaction vessel (the temperature of the mixed solution) was maintained at 50°C. While stirring at 300 rpm, a solution (B) containing 88g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22g of methanol and a solution (C) containing 21g of pure water were added and mixed to prepare a mixed solution for the synthesis reaction.
[0220] The rate of addition of liquid (B) relative to 1 mol of water contained in liquid (A) is 2.0 × 10⁻⁶ in silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0221] The synthesis reaction was completed by adding the full amounts of liquids (B) and (C), resulting in a mixture containing silica particles. The presence of silica particles in the mixture was confirmed by measuring the average longest diameter and average secondary diameter of the primary silica particles, as well as the concentration of silica particles in the mixture. The average longest diameter of the primary silica particles was 16 nm. The average secondary diameter of the formed silica particles was 19 nm. The concentration of silica particles in the mixture was 2.2% by mass.
[0222] (Conductivity increase process)
[0223] The conductivity of the mixture obtained in the silica particle formation process was measured (the conductivity of the mixture at the start of the conductivity increase process). After measurement, the mixture was stirred at 300 rpm while being cooled to 30°C for 90 minutes to obtain a mixture with increased conductivity. The conductivity of the mixture was measured again at the point where the temperature reached 30°C (the conductivity of the mixture at the end of the conductivity increase process). The conductivity of the mixture at the end of the conductivity increase process increased by 134% compared to the start of cooling (= conductivity of the mixture at the end of the conductivity increase process / conductivity of the mixture at the start of the conductivity increase process × 100).
[0224] (Silica particle growth process 1)
[0225] For the mixture obtained in the conductivity increase process, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C, and while stirring at 300 rpm, liquid (B) containing 88 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22 g of methanol and liquid (C) containing 21 g of pure water are continuously added to allow the reaction to proceed.
[0226] The addition rate of liquid (B) was set relative to 1 mol of water contained in liquid (A), which is equivalent to 2.0 × 10⁻⁶ silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0227] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 4.0% by mass.
[0228] (Silica particle growth process 2)
[0229] For the mixture obtained in the silica particle growth process 1, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C. While stirring at 300 rpm, liquid (B) containing 379 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 95 g of methanol and liquid (C) containing 90 g of pure water are added continuously to carry out the reaction.
[0230] The addition rate of liquid (B) was set relative to 1 mol of water contained in liquid (A), which is equivalent to 5.0 × 10⁻⁶ silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0231] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 9.5% by mass.
[0232] (Water replacement process)
[0233] The mixture obtained in step 2 of the silica particle growth process is heated to a boiling point under normal pressure. During heating, pure water is added while maintaining a constant liquid level to induce distillation, thereby replacing the methanol in the mixture with pure water to obtain silica sol.
[0234] <Example 4>
[0235] (Silica particle formation process)
[0236] In a 3L reaction vessel equipped with a stirrer and a cooling function, a solution (A) containing 1355g of methanol (manufactured by Kanto Chemical Co., Ltd.) mixed with 57g of pure water and 65g of 29% ammonia was added. The temperature of the liquid in the reaction vessel (the temperature of the mixed solution) was maintained at 30°C. While stirring at 300 rpm, a solution (B) containing 88g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22g of methanol and a solution (C) containing 21g of pure water were added and mixed to prepare a mixed solution for the synthesis reaction.
[0237] The rate of addition of liquid (B) relative to 1 mol of water contained in liquid (A) is 2.0 × 10⁻⁶ in silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0238] The synthesis reaction was carried out by adding the complete amounts of liquids (B) and (C), resulting in a mixture containing silica particles. The presence of silica particles in the mixture was confirmed by measuring the average longest diameter and average secondary diameter of the primary silica particles, as well as the concentration of silica particles in the mixture. The average longest diameter of the primary silica particles was 21 nm. The average secondary diameter of the formed silica particles was 20 nm. The concentration of silica particles in the mixture was 2.1% by mass.
[0239] (Conductivity increase process)
[0240] The conductivity of the mixture obtained in the silica particle formation process (the conductivity of the mixture at the start of ammonia addition) was measured. After measurement, the temperature of the mixture was maintained at 30°C, and while stirring the mixture at 300 rpm, 49 g of 29% (w / w) ammonia solution was added in one go (liquid D), and stirring was continued. After adding liquid D, when the conductivity of the mixture increased to 114% compared to the conductivity of the mixture at the start of ammonia addition, the next silica particle growth process 1 was initiated.
[0241] (Silica particle growth process 1)
[0242] For the mixture obtained in the conductivity increase process, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C, and while stirring at 300 rpm, liquid (B) containing 88 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 22 g of methanol and liquid (C) containing 21 g of pure water are continuously added to carry out the synthesis reaction.
[0243] The addition rate of liquid (B) was set relative to 1 mol of water contained in liquid (A), which is equivalent to 2.0 × 10⁻⁶ silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0244] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 3.9% by mass.
[0245] (Silica particle growth process 2)
[0246] For the mixture obtained in the silica particle growth process 1, the liquid temperature (mixture temperature) in the reaction vessel is maintained at 30°C. While stirring at 300 rpm, liquid (B) containing 379 g of tetramethoxysilane (TMOS, manufactured by Tama Chemical Industry Co., Ltd.) dissolved in 95 g of methanol and liquid (C) containing 90 g of pure water are added continuously to carry out the reaction.
[0247] The rate of addition of liquid (B) relative to 1 mol of water contained in liquid (A) is 5.0 × 10⁻⁶ in silicon atoms. -3 mol / min. Liquid (C) is added at a rate of 2 mol / min relative to 1 mol of tetramethoxysilane added to liquid (B).
[0248] The reaction was completed by adding the full amounts of liquids (B) and (C) to obtain a mixture that grows silica particles. The concentration of silica particles in the mixture was 9.3% by mass.
[0249] (Water replacement process)
[0250] The mixture obtained in step 2 of the silica particle growth process is heated to a boiling point under normal pressure. During heating, pure water is added while maintaining a constant liquid level to induce distillation, thereby replacing the methanol in the mixture with pure water to obtain silica sol.
[0251] <Comparative Example 1>
[0252] In a 5L reaction vessel equipped with a stirrer and a cooling function, a solution (A) containing 375.92g of pure water, 108g of 29% ammonia and 91g of colloidal silica (silica concentration: 12% by mass, average secondary particle size: 25nm) was added to 2945g of methanol. While stirring at 300rpm, the temperature of the liquid in the reaction vessel was maintained at 20°C, and a solution (B) containing 309g of tetramethoxysilane (TMOS) dissolved in 79g of methanol was added at 11mL / min to prepare the reaction solution and obtain silica sol.
[0253] <Comparative Example 2>
[0254] The addition rate of liquid (B) was changed from 11 mL / min to 5.5 mL / min, and otherwise silica sol was obtained in the same manner as in Comparative Example 1.
[0255] In the methods for manufacturing silica sols of Examples 1-4 and Comparative Examples 1-2, the amounts and conditions of raw materials used are summarized in Tables 1-4. Table 5 shows the concentration of silica particles, the average primary particle size of silica particles, the average aspect ratio, the ratio of the number of silica particles with an aspect ratio of 1.50 or more to the total number of silica particles, the average sphericity, and the ratio of the number of silica particles with a sphericity of 0.90 or more to the total number of silica particles in the silica sols of Examples 1-4 and Comparative Examples 1-2.
[0256] [Table 1]
[0257]
[0258] [Table 2]
[0259]
[0260] [Table 3]
[0261]
[0262] [Table 4]
[0263]
[0264] [Table 5]
[0265]
[0266] As shown in Table 5, the silica particles in the silica sols of Examples 1-4 have a high average aspect ratio of 1.50 or more compared to the silica sols of Comparative Examples 1-2. In the silica sols of Examples 1-4, the number of silica particles with an aspect ratio of 1.50 or more is more than 40% of the total number of silica particles. Therefore, the silica sols of Examples 1-4 contain a large number of silica particles with a high aspect ratio.
[0267] As shown in Table 5, the silica particles in the silica sols of Examples 1-4 have a low average sphericity of 0.80 or less compared to the silica sols of Comparative Examples 1-2. In the silica sols of Examples 1-4, the number of silica particles with a sphericity of 0.90 or more, calculated based on images observed by a scanning electron microscope, is less than 40%. Therefore, it can be concluded that the silica sols of Examples 1-4 contain a large number of irregularly shaped silica particles.
[0268] As shown in Table 5, it can be seen that the silica sols of Examples 1-4 have a higher concentration of silica particles compared to the silica sols of Comparative Examples 1-2.
[0269] This application is based on Japanese Patent Application No. 2025-045714, filed on March 19, 2025, the entire disclosure of which is incorporated herein by reference.
Claims
1. A method for manufacturing silica sol, comprising: A liquid (B) is continuously or intermittently mixed into a liquid (A), wherein the liquid (A) comprises an alkaline catalyst, water, and a first organic solvent, and the liquid (B) comprises at least one of a tetramethoxysilane and its condensate, and a second organic solvent. The mixing process includes: increasing the electrical conductivity of the mixture after forming silica particles in the mixture.
2. The manufacturing method according to claim 1, wherein, The increase in the conductivity of the mixture is achieved by increasing the amount of ions from the alkaline catalyst in the mixture.
3. The manufacturing method according to claim 1 or 2, wherein, The increase in the conductivity of the mixture is achieved by decreasing the temperature of the mixture.
4. The manufacturing method according to claim 1 or 2, wherein, The increase in the conductivity of the mixture is achieved by adding a liquid (D) containing ammonia to the mixture.
5. The manufacturing method according to claim 1 or 2, wherein, The mixing further includes mixing a water-containing liquid (C) into at least one of the liquid (A) and the mixture.
6. The manufacturing method according to claim 1 or 2, wherein, The conductivity of the mixture increases by more than 110%.
7. The manufacturing method according to claim 1 or 2, wherein, The average secondary particle size of the silica particles that increases the conductivity of the mixture is between 5 nm and 300 nm.
8. A silica sol comprising silica particles having an average aspect ratio of 1.50 or more, wherein the number of silica particles having an aspect ratio of 1.50 or more is 40% or more relative to the total number of silica particles, and the concentration of the silica particles is 4% by mass or more.
9. The silica sol according to claim 8, wherein, The number of silica particles with a sphericity of 0.90 or higher accounts for less than 40% of the total number of silica particles.
Citation Information
Patent Citations
Manufacturing method for silica sol
JP2018168031A
System
JP2025045714A
Method for producing silica sol
US20200377371A1